AB1185 BUDGET IMPACT ANALYSIS OF INTRODUCING SUBCUTANEOUS INFLIXIMAB CT-P13 SC FROM THE UK PAYER PERSPECTIVE. (2nd June 2020) - Perry, M.; Jang, M.
Abstract : Background: CT-P13 subcutaneous (SC) is the first and only SC version of infliximab developed by Celltrion Healthcare and currently approved by the European Medicines Agency (EMA) for the treatment of rheumatoid arthritis (RA). Infliximab has been only available in intravenous (IV) formulation and thus this new mode of administration will allow patients to self-inject at homes. Self-injection will reduce number of outpatient visits and expected to decrease IV administration cost significantly. This research describes the economic impact of introducing infliximab SC from the UK payer perspective. Objectives: The budget impact analysis (BIA) was conducted to assess the financial impact of the adoption of infliximab SC. The BIA calculates the costs of treatment (drug acquisition cost and administration) for patients with RA as first-line treatments, and compares the cost in a scenario without infliximab SC vs a scenario with infliximab SC to estimate the budget impact over the 5 year period. Methods: A prevalence-based BIM was developed incorporating epidemiological data, administration cost data from the literature and market share data from IQVIA. The analysis compared a market scenario where a proportion of patients were treated with infliximab SC ('World With' infliximab SC) to an alternative market scenario where infliximab SC were not available and all patients were treated with IV ('World Without' infliximab SC). The model assumed that the clinical outcomes are same between infliximab SC and infliximab IV, and patients entering the model were all naïve and remained in the treatment for 5 years. In the 'World With' scenario, patients receiving infliximab IV switched to SC administration at 30% in Year 1, 45% in Year 2, and remained 60% from Year 3 to 5. The drug cost of infliximab SC is assumed to be the same as that of comparator treatments. Administration cost per infliximab IV infusion was estimated to be ₤382 and ₤3.32 per SC administration. Results: Compared to the "World Without" infliximab SC, the introduction of subcutaneous infliximab resulted in cost savings of ₤39.6 million in UK over a 5-year period, equating to 4, 466 additional patients to be treated with infliximab SC in base case scenario. Sensitivity analysis includes dose-escalation up to 5mg/kg to reflect the real-world setting. In that scenario, the saving increases to ₤279.6 million over a 5-year period, equating to 30, 839 additional patients to be treated with infliximab SC. Conclusion: Utilization of subcutaneous infliximab may lead to substantial cost savings for UK payers. Self-injection will significantly reduce the burden on healthcare delivery allowing resource to be spent elsewhere. Sensitivity analysis concluded that treatment with increased IV dose will result in higher savings from switching patients to subcutaneous infliximab. References: [1]European Medicines Agency. Remsima SC authorization details. https://www.ema.europa.eu/en/documents/product-information/remsima-epar-product-information_en.pdf [2]Carpenter, L., et al. (2014). Patients with Moderate Disease Activity in the First 5 Years of Rheumatoid Arthritis Still Progress Radiographically Despite Conventional Disease Modifying Therapy.: 2135. Arthritis & Rheumatology, 66 . [3]The NICE British National Formulary (BNF). https://bnf.nice.org.uk/medicinal-forms/ [4]Tetteh, E. K., & Morris, S. (2014). Evaluating the administration costs of biologic drugs: development of a cost algorithm. Health economics review, 4(1), 26. [5]National Institute for Health and Care Excellence. (2016). Adalimumab, etanercept, infliximab, certolizumab pegol, golimumab, tocilizumab and abatacept for rheumatoid arthritis not previously treated with DMARDs or after conventional DMARDs only have failed. Disclosure of Interests: Martin Perry Grant/research support from: Grifols, Abbvie, Sandoz unrestricted educational grant, Consultant of: Abbvie, Gilead, Celltrion Advisory Board, Speakers bureau: Sandoz, Minyoung Jang Employee of: HEOR & Market access specialist in Celltrion Healthcare